Efficacy and Safety of Subarachnoid Block among 8 to 14 years Old Children: A Retrospective Observational Study - Ali, Mohammad; Johora, Fatema (Journal of Brahmanbaria Medical College, 2026)
Background: Subarachoid Block (SAB) has been practicing as pediatric anesthesia from the very begining but still not popular in Bangladesh. There are all lots of fallacies regarding efficacy and safety of SAB in pediatric age guoup. Current study was carried out to assess the efficacy and safety of SAB among children of 8-14 years. Materials & methods: This retrospective observational study was conducted in M A Rashid Hospital, Jamalpur from May 2023 to October 2023 by analyzing data of 32 patients (8-14 years) of ASA grading I who underwent different lower andominal and lower extremity surgeries under SAB. All the patients were evaluated following standard protocol in pre anesthetic checkup room Children were sedated with Inj. Ketamine 10 mg I/V along with Inj. Midazolam 1mg I/V. SAB was given with 25G spinocaine needle at the level of L4/L5 with 0.5% Bupivacaine hyperbaric 1.5 ml (7.5 mg) following local anesthetic (lidocaine 1% 1 ml) infiltration at the site of SAB in left lateral position. Demographic characteristics, type of surgery, duration of surgery, outcome of SAB, perioperative vital parameters (Pulse rate, systolic blood pressure, diastolic blood pressure, SPO2, ECG) characteristics of sensory and motor block, duration upto first pain complain and complication were recorded as study data by analyzing anesthesia documents and postoperative records. Results: Mean age of the study population was 10.00 ± 2.02 years, 53.13% patients were male and all the patients were from ASA grading I. Mean operative time for surgeries was 33.59± 11.23 minutes. Circumcision (40.63%) was the commonest procedure. Success rate of SAB was 100%. Onset and duration of sensory block was 5± 2.0 minutes and 120.23± 12.34 minutes respectively. Onset of motor block could not be assessed as patients were sedated. And duration of motor block was 112.19± 12.76 minutes.Time duration for first complain of pain was 150.31± 14.64 minutes. Vital parameters of studied population were stable in perioperative period. There was not a single incidence of complication like nausea, vomiting, itching, chest pain, restlessness, shivering, urinary retention, neurological complications, Post Dural Puncture Headache (PDPH). Conclusion: Subarachnoid block could be an effective and safe alternative for the anesthetic management of pediatric patients while performed by experienced anesthesiologist. Journal of Brahmanbaria Med. Coll. Volume 07 Issue 01 Jan 2025 ; 25-29